RiskAnalytics: An R package for real time processing of Nasdaq and Yahoo finance data and parallelized quantile lasso regression methods - Lukas Borke (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2017)
In order to integrate and facilitate the research, calculation and analysis methods around the Financial Risk Meter (FRM) project, the R package RiskAnalytics has been developed. Its main goal is to provide data processing and parallelized quantile lasso regression methods for risk analysis based on NASDAQ data, Yahoo Finance data and some macro variables. The derived "Risk Analytics" can help to forecast and evaluate the systemic risk for the corresponding markets. The visualization and the up-to-date FRM can be found on http://frm.wiwi.hu-berlin.de. Supplementary R codes are published on www.quantlet.de with the keyword FRM. The RiskAnalytics package is a convenient tool with the purpose of integrating lasso penalized quantile regression methods with full solution paths and cluster computing support around the topic "Risk Analytics and FRM".
Keywords: C21; C51; G01; G18; G32; G38; 330; Risk Analytics; FRM; Data Analytics; Systemic Risk; Quantile Regression; Lasso; Value at Risk; Parallel and Cluster Computing; EDA; Data Visualization